Application of Nanomaterial-Mediated Ferroptosis Regulation in Kidney Disease - Zhu J; Zhang Z; Chu Y; Xie Z; Zeng D; Jin L; Li L (International Journal of Nanomedicine)
Jiamin Zhu,1,* Zhen Zhang,1,2,* Yanhui Chu,1,* Zhongyin Xie,1 Dongmei Zeng,1 Lijiao Jin,1 Luxin Li1 1Heilongjiang Key Laboratory of Anti-Fibrosis Biotherapy, Mudanjiang Medical University, Mudanjiang, People’s Republic of China; 2School of First Clinical Medical College, Mudanjiang Medical University, Mudanjiang, People’s Republic of China*These authors contributed equally to this workCorrespondence: Luxin Li, Heilongjiang Key Laboratory of Anti-Fibrosis Biotherapy, Mudanjiang Medical University, Mudanjiang, 157000, People’s Republic of China, Tel +86 13763617174, Email liluxin@mdjmu.edu.cnAbstract: Kidney diseases are a significant global cause of death and disability, resulting from the destruction of kidney structure and function due to an imbalance between the death of renal parenchymal cells and the proliferation or recruitment of maladaptive cells, caused by various pathogenic factors. Currently, therapies and their efficacy for kidney diseases are limited. Ferroptosis is a newly discovered iron-dependent regulated cell death. The imbalance of iron homeostasis and lipid metabolism affects the occurrence and progression of kidney diseases by triggering ferroptosis, which is considered an important target for the development of kidney disease drugs. However, in clinical practice, targeted ferroptosis therapy for kidney diseases faces obstacles such as poor drug solubility, low drug resistance, and imprecise targeting. With the rapid development of nanomaterials in the medical field, new opportunities have emerged for the precise regulation of ferroptosis in the treatment of kidney diseases. This article provides a detailed introduction to the regulatory mechanisms of ferroptosis, the properties of nanomaterials, and their application in the treatment of kidney diseases, with a focus on discussing the mechanisms of action and therapeutic potential of nanomaterials based on ferroptosis regulation in kidney diseases. The aim of this article is to provide new ideas and directions for future kidney disease treatments. Keywords: nanomaterial, nanomedicine, ferroptosis, kidney disease